The Past, Present, and Future of Parkinson’s Disease Treatment - Park, Soyeon (Open Science Journal, 2020)
Parkinson’s Disease was first introduced by James Parkinson in 1817. Since then, major strides have been made in the development of its treatment. Early treatments were dominated by traditional and complementary therapies, which were largely serendipitous and observation-based. Especially, the use of anticholinergics by Jean-Martin Charcot and his student Ordenstein prevailed in the late 20th century. Current drug-based therapies manifest in the form of levodopa accompanied by dopamine agonist, COMT inhibitor, or MAO-B inhibitor, for the purpose of reducing the levodopa-induced symptom fluctuation. In terms of surgical treatment, while ablative surgeries in the brain have been abandoned due to high mortality rate in the late 1900s, Deep Brain Stimulation in the subthalamic nucleus or internal globus pallidus has mostly replaced ablative surgeries since its introduction in 1987. Current research topics include non-dopaminergic agents for motor fluctuation reduction, transplantation of dopaminergic neurons, gene therapies using viral vectors, reduction of alpha-synuclein neurotoxicity, and neuroprotective therapies. Especially, due to the fact that the etiology of the disease is yet to be elucidated, neuroprotective therapies aimed at slowing or stopping disease progression are of particular interest. It is suggested that future research should aim towards clarifying the cause of the disease, for the development of a treatment that can permanently halt or reverse Parkinson’s Disease-related neurodegeneration.